Uso de cinzas brutas de bagaço de cana-de-açúcar como material substitutivo no concreto - Wesley Silva de Oliveira (2021)
The study presents an overview of the use of sugarcane bagasse ash ("bottom ashes" type), originated in cogenerators, with the purpose of application in structural concrete. Based on the need to characterize the concretes that use ash, and the growing environmental concern, which encourages the efficient use of materials and the reuse of waste, it’s presented a systematic literature review and the use of raw ash as a replacement material in concrete, to corroborate the possibility of turning the residue into a co-product. Replacements of Portland cement, in contents of 5, 10 and 15%, caused average compressive strength gains of 1, 25 and 9%, and average tensile strength gains of 3, 11 and 8%, respectively. The modulus of elasticity for these concretes was about 20% lower than the concrete with no material replacement, however the values raged from 15 to 40% higher than the estimated values. The void indices and absorption rates showed values below 20 and 10%, respectively, indicating good durability of the concretes. For the production of prismatic structural elements, the maximum savings potential from replacements of cement in concrete in 5, 10 and 15%, are 8, 25 and 18%, respectively. It was verified that the replacement of cement by raw sugarcane bagasse ash is technically and economically viable for all tested contents. On the other hand, the replacement of sand by ash only presents good results when accompanied by the addition of crystallizers. Although, this kind of replacement incorporates greater volumes of waste, which is desirable from an environmental perspective.